DataPolitics Zum Umgang mit Daten im digitalen Zeitalter - Bachor, Martina; Hug, Theo; Pallaver, Günther (innsbruck university press, 2021)
In our interaction with digital systems, we produce a great deal of data every day, which can be used for economic purposes as well as for political purposes. While democratic systems in Europe are looking for ways to deal with these personal traces as securely, anonymously and effectively as possible, data can also be used for political and social control, of which China is an example. This anthology contains contributions on current questions about opportunities and dangers of the political use of data. The contributions cover data-driven campaigning, the "naturalisation" of personal data production, the democratisation of digital control, data activism and digital citizenship, as well as digital literacy and the responsible use of educational data.